Sex steroid receptors and apoptosis-related proteins are differentially expressed in polycystic ovaries of adult dogs - Chuffa, Luiz Gustavo de Almeida [UNESP]; Lupi Júnior, Luiz Antonio [UNESP]; da Maia Lima, Alfredo Feio [UNESP] (Elsevier, 2015)
In Polycystic Ovaries (PCOs), the dynamics of sex hormone receptors and follicle-related apoptotic signaling remain unknown. In this study, we investigated the expression of androgen receptors (AR), estrogen receptors (ERα and ERβ), and apoptosis-related molecules (BAX, active caspase-3, Bcl-2 and Survivin) on different follicular stages of PCOs in adult dogs. Clinical evidences of high estradiol and testosterone levels, persistent estrus and vaginal discharge were observed. Inhibin B immunolabeling was increased in primary and 2 to 5-mm follicles, and a marked epithelial hyperplasia was common in the ovarian surface. Ovarian epithelia and primary follicles showed low expression of AR, ERα, and ERβ, whereas a moderate immunoexpression of AR was found in theca cells of secondary follicles and cysts. In PCOs, growing follicles displayed ERα expression, and secondary follicles exhibited higher ERβ expression. In addition, while few ERα-positive cells were found in the cysts, ERβ was moderately expressed in growing follicles and cysts. BAX was upregulated in the ovarian epithelium, primary follicles, and in the wall of follicular cysts. Active caspase-3 was significantly downregulated in the epithelium, primary follicles, and follicular cysts, whereas growing follicles had a strong immunoexpression in the granulosa cells. Bcl-2 and survivin were increased in the epithelium and primary follicles, and only survivin was upregulated in secondary and growing follicles. While Bcl-2 had a diffuse immunexpression in the follicular cysts, survivin was overexpressed by these cells. We concluded that sex steroid receptors and apoptotic proteins are differentially expressed in the follicles of adult dogs with PCOs.
Keywords: Apoptosis; AR; Dog; ER; Polycystic ovary; Sex steroid receptors